The roof depth of the transition zone between upper and lower Earth's mantle - Gordienko, V.V. (Reports of the National Academy of Sciences of Ukraine, 2018)
The experimental and calculated values of the roof depth of the transition zone between the upper and lower mantle of the Earth are compared. It is proved that this boundary corresponds to the beginning of polymorphic transformations of mantle's rocks. The magnitude of the jump in the velocity of longitudinal seismic waves at a level of 0.45 km/s is estimated. Changes in the depth of the roof due to temperature variations under the influence of the active heat and mass transfer according to the scheme of the advection-polymorphic hypothesis are studied. The approximate correspondence of the results (within the limits of calculation errors) to experimental data in different regions of the continents is demonstrated. Under the oceans, the situation remains uncertain now, mainly due to the differences in the experimental data of different authors.